Uirapuru Centro de Artes: proposta de reabilitação arquitetônicapara uma escola de artes e galeria no Centro Histórico de Belém-Pa - FURTADO, Giulia Gama Tobias (2023)
The building object of this study is located in an urban center of great historical importance for the evolution of the city of Belém in the state of Pará. Former headquarters of FUNPAPA and, later, of FUMBEL, the building is abandoned, bringing risks. For the resident and working population of its surroundings, it currently presents traces of the Art Noveau style. Given this, this work consists of the architectural proposal of building rehabilitation for a Cultural Center and Artistic Education, based on studies on contemporary restoration theorists, such as Cesare Brandi, Moreno Navarro and Muñoz-Viñas, of the applied legislation on this urban area. and the historical context and stylistic evolution of the building. In addition, the project must obey aesthetic guidelines that enhance the artistic culture and regional flora.